Comparing Alteration of MMSE (Mini-Mental State Examination) Scores as Cognitive Function Test in Geriatrics After General and Regional Anesthesia - Budianto, Ferrie; Setiawan, Philia; Hamzah, Hamzah; Yulianti, Erikavitri (Faculty of Medicine-Universitas Airlangga, 2020)
Introduction: An alteration of cognitive function in geriatrics often occurred after a surgery procedure. To do a surgery, patients would go through the process with anesthesia, whether it is general or regional anesthesia. We aimed to identify the effect of general and regional anesthesia in increasing the risk of alteration in cognitive function from geriatrics who underwent elective surgery followed by other risks. Methods: This observational analytic study has a total sample of 60 patients who aged 60 years or more, and half of the total sample underwent an elective surgery with general anesthesia, whereas the other half with regional anesthesia at Gedung Bedah Pusat Terpadu Dr. Soetomo General Hospital in a range of October – November 2016. The cognitive function of patients was assessed with MMSE which is done in approximately 10 – 15 minutes. Results: There was a statistically significant correlation between age and both preoperative MMSE score also the alteration of MMSE score after 3 days in patients with regional anesthesia (P-value = 0.032; 0.044). Also, the correlation between educational status and preoperative MMSE score (P-value = 0.001). There was also a statistically significant difference in alteration of the MMSE score after 3 days between patients with general and regional anesthesia which went through the hypotension phase (P-value = 0.022; 0.003). We identified that both general and regional anesthesia could lead to alteration of MMSE score (P-value = 0.001; 0.02) and there was a statistically significant difference between both of them (P-value = 0.001). Conclusion: Both general and regional anesthesia could lower the cognitive function of geriatrics, especially general anesthesia which happened to have a higher risk to occur. Other factors such as age, educational status, and hemodynamic condition during surgery, had their impacts toward lowering cognitive function in geriatrics.